Neuronal nitric oxide synthase (NOS1) and its adaptor, NOS1AP, as a genetic risk factors for psychiatric disorders. (January 2015) - Freudenberg, F.; Alttoa, A.; Reif, A.
<x xml:space="preserve">Abstract</x> Nitric oxide (NO) is a gaseous transmitter produced by nitric oxide synthases (NOSs). The neuronal isoform (NOS‐I, encoded by NOS1) is the main source of NO in the central nervous system (CNS). Animal studies suggest that nitrinergic dysregulation may lead to behavioral abnormalities. Unfortunately, the large number of animal studies is not adequately reflected by publications concerning humans. These include post‐mortem studies, determination of biomarkers, and genetic association studies. Here, we review the evidence for the role of NO in psychiatric disorders by focusing on the human NOS1 gene as well as biomarker studies. Owing to the complex regulation of NOS1 and the varying function of NOS‐I in different brain regions, no simple, unidirectional association is expected. Rather, the 'where, when and how much' of NO formation is decisive. Present data, although still preliminary and partially conflicting, suggest that genetically driven reduced NO signaling in the prefrontal cortex is associated with schizophrenia and cognition. Both NOS1 and its interaction partner NOS1AP have a role therein. Also, reduced NOS1 expression in the striatum determined by a length polymorphism in a NOS1 promoter (NOS1 ex1f‐VNTR) goes along with a variety of impulsive behaviors. An association of NOS1 with mood disorders, suggested by animal models, is less clear on the genetic level; however, NO metabolites in blood may serve as biomarkers for major depression and bipolar disorder. As the nitrinergic system comprises a relevant target for pharmacological interventions, further studies are warranted not only to elucidate the pathophysiology of mental disorders, but also to evaluate NO function as a biomarker.